Performance Evaluation of Malt Barley (Hordeum vulgare L.) Varieties for Yield and Quality Traits in Eastern Amhara Regional State, Ethiopia - Abebe Assefa; Getawey Girmay; Tesfaye Alemayehu; Alemu Lakew (Advances in Agriculture)
Barley (Hordeum vulgare L.) is an annual cereal crop that belongs to the grass family Poaceae of the tribe Triticeae. Due to the establishment and production capacity of malt and beer factories in Ethiopia, malt barley production demand increased from time to time. Eight released malt barley varieties were evaluated in four environments in Wag-himra and Lasta districts in the main production season for two years (2016 and 2017). The objective of the trial was to identify a high yielder and standard-quality malting barley variety for production. The trial was conducted using a randomized complete block design with three replications on a plot size of 1.2 m width with that of 2.5 m length. The results revealed that there was a highly significant difference in grain yield and quality traits (p<0.05). The kernel protein and starch content of the varieties ranged from 9.85 to 11 and 63–65%. The thousand kernel weight of the varieties was in the range of 32.5 to 46.4 g. EH1847 (3340 kg ha−1), IBON174/03 (3351 kg ha−1), and Bahati (3220 kg ha−1) were the first three best performing high yielder and best varieties that fulfilled quality parameter requirements set by the National Standard Authority for malting barley. Therefore, these varieties are recommended for production in the Wag-himra and Lasta agroecologies for their high yield, kernel size, and kernel protein content. Further study is required on agronomic practices and brewing quality attributes in malt barley.